Contribution of long-term dysphagia monitoring to first line treatment of head and neck cancer patients - Falewee, Marie Noëlle; Hebert, Christophe; Benezery, Karen; Bozec, Alexandre; Guigay, Joël; Chamorey, Emmanuel; Michel, Cécile (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Dysphagia is a serious sequel of head and neck cancer (HNC) and its treatment. This dysfunction is frequent and likely underreported by clinical exam. It seems necessary to assess its global burden during the pre, per and post treatment periods (up to 18 months), regardless of the treatment received. Methods: This was a prospective cohort study assessing the rate of dysphagia in first-time treated HNC patients, using the deglutition handicap index questionnaire (DHI) and the clinician reporting. Time to occurrence, severity and length of the dysfunction were recorded. The benefit of an evaluation by the patient himself was investigated. Results: Of 134 evaluable patients: 22 were treated by surgery alone (16.4%), 16 by radiotherapy (RT) alone (11.9%), 3 by chemotherapy (CT) alone (2.2%), 28 by RTCT (20.9%), 31 by induction chemotherapy followed by RTCT (23.1%), 11 by surgery+RT (8.2%) and 23 by surgery+RTCT (17.2%). Patients completed 87.9% of the expected DHI. The dysphagia frequency reported was 92.2% by patient-reporting and 80.9% by clinicians-reporting, whatever the intensity. Self-perceived moderate to severe dysphagia was reported in 69.8% of patients. Conclusions: Given the strong impact of dysphagia on the quality of life and prognosis of HNC patients, it appears essential to perform screening and systematic monitoring. Using a simple and well accepted questionnaire, such as DHI, which is also well correlated with clinical evaluation, we demonstrated a significant frequency of dysphagia. The use of real-time patient-reported outcomes for its early detection would be an asset, particularly during long-term follow-up. Registered under ClinicalTrials.gov Identifier no. NCT03068559.